Advanced testing of the LoT hypothesis by social reasoning - Grüning, David (Behavioral and brain sciences, 2023)
I elaborate on Quilty-Dunn et al.'s integration of the language-of-thought hypothesis in social reasoning by outlining two discrepancies between the experimental paradigms referred to by the authors and the social world: Self-referential projection and deliberate thinking in experiments. Robust tests of the hypothesis in social reasoning should include observational, natural, and cross-cultural approaches.
Gesehen am 13.11.2023